HARMONISASI KONSEP PENDIDIKAN MUHAMMAD ATHIYAH AL-ABRASI DAN HADITS MAKARIM AL-AKHLAQ DALAM KONTEKS PENDIDIKAN ISLAM MODERN: ANALISIS RELEVANSI DAN IMPLEMENTASI - lbs, Freddy Hermansyah; Srg, Syahruddin (Atta'dib Jurnal Pendidikan Agama Islam, 2024)
This research aims to evaluate the relevance of the concept of Moral Education according to Muhammad Athiyah Al-Abrasi and the hadith about makarim al-akhlak in the context of Islamic education to date. By using library research methods and data collection techniques through documentation, this research draws data from literature that is considered still relevant to the research theme. The research results show that the concept of Moral Education taught by Al-Abrasi and the principles contained in the hadith regarding makarim al-akhlak still have strong relevance in the world of Islamic Education in the modern era.